Distributed core multicast (DCM) a multicast routing protocol for many groups with few receivers. - Blazević, Ljubica (Computer communication review.)
We present a multicast routing protocol called Distributed Core Multicast (DCM). It is intended for use within a large single Internet domain network with a very large number of multicast groups with a small number of receivers. Such a case occurs, for example, when multicast addresses are allocated to mobile hosts, as a mechanism to manage Internet host mobility or in large distributed simulations. For such cases, existing dense or sparse mode multicast routing algorithms do not scale well with the number of multicast groups. DCM is based on an extension of the centre-based tree approach. It uses several core routers, called Distributed Core Routers (DCRs) and a special control protocol among them. DCM aims: (1) avoiding multicast group state information in backbone routers, (2) avoiding triangular routing across expensive backbone links, (3) scaling well with the number of multicast groups. We evaluate the performance of DCM and compare it to an existing sparse mode routing protocol when there is a large number of small multicast groups. We also analyse the behaviour of DCM when the number of receivers per group is not a small number.